Socio-Cultural Impact of Virtual Reality Technology on Art Appreciation and Cultural Engagement - Kwame, Jaymike (International Journal of Humanity and Social Sciences, 2023)
Purpose: The main objective of this study was to explore the socio-cultural impact of virtual reality technology on art appreciation and cultural engagement. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the socio-cultural impact of virtual reality technology on art appreciation and cultural engagement. The empirical review revealed that in the wake of rapid technological advancements, virtual reality technology has emerged as a powerful tool in transforming the landscape of art appreciation and cultural engagement. Through a synthesis of empirical studies, it is evident that VR has brought about profound changes, unlocking new dimensions of artistic experiences and redefining cultural engagement paradigms. Virtual reality has succeeded in reinvigorating art appreciation, transcending the boundaries of physical space and time. Users are now able to immerse themselves fully in artworks, experiencing them in ways that were previously unimaginable. Unique Contribution to Theory, Practice and Policy: The Cultural Proximity theory, Technology Acceptance Model (TAM) and the Cultural Capital theory may be used to anchor future studies on the socio-cultural impact of virtual reality technology on art appreciation and cultural engagement. The study recommended that cultural institutions and art organizations should actively integrate virtual reality technology into their exhibits and educational programs. A concerted effort must be made to ensure that virtual reality remains inclusive and accessible to all individuals, including those with disabilities. Ethical guidelines and regulations should be established to govern the collection and use of user data in virtual reality experiences. Emerging artists should embrace virtual reality as a means to gain exposure and access new audiences.